Habilidades comunicativas en lengua indígena Murui Muinan + e idioma castellano en niños de la institución educativa inicial N°409 Negro Urco, Santa Clotilde 2024 - Sanchez Lopez, Letty Deysi (2025)
The objective of this study was to compare communication skills in the indigenous Murui language and in the Spanish language among children from the Initial Educational Institution No. 409 Negro Urco Santa Clotilde during the year 2024. The research covered a sample of 40 children from said institution. From a methodological perspective, a comparative approach was adopted with a cross sectional, field and univariate design. For data collection, two communication skills tests were applied, one in Spanish and another in the Murui language, both validated by experts in the area. In conclusion, the results show a notable disparity in the performance of communication skills. 100% of the children reached the outstanding achievement level in Spanish, while only 20.0% achieved the same level in the indigenous Murui language, with additional percentages that reflect poor performance in the achieved, in process and beginning categories. These findings indicate that Spanish proficiency is significantly higher, which highlights the need to implement educational strategies that strengthen the learning and use of the indigenous Murui language, thus promoting a more balanced and culturally inclusive education.